Relationship between land cover and biophysical parameters in the Brazilian Savana - Martins, Alécio Perini; Galvani, Emerson (Revista do Departamento de Geografia, 2020)
Land use and land cover is essential in regulating the water cycle and influences the evapotranspiration process. Land use and land cover changes will directly affect the balance of radiation by changing three biophysical parameters: albedo, NDVI and the surface temperature. This research aims at evaluating the relationship between land use and land cover and biophysical parameters involved in the estimation of heat flows and real evapotranspiration. These parameters were estimated using SEBAL (Surface Energy Balance Algorithms for Land), an essentially mathematical model that requires a few data collected on the surface for calibration. The study area comprises seven watersheds located in significant areas of the Southwest of Goiás State and Northwest of Mato Grosso do Sul State, Cerrado biome, with great diversity of land cover where areas of soy and corn production and livestock predominate. The surface temperature was identified as the biophysical parameter with the highest correlation with the balance of radiation, heat flows and evapotranspiration, with determination coefficients greater than 80%. The albedo, despite having a coefficient of determination in the range of 60%, also proved to be an important indicator of environmental changes with direct effects on the water cycle. The statistics also indicates that SEBAL is effective for estimating evapotranspiration in large areas, with diversity of land cover and few monitoring points.